Phosphonic Acids on an Atomically Defined Oxide Surface: The Binding Motif Changes with Surface Coverage - Schuschke, Christian; Schwarz, Matthias; Hohner, Chantal; Silva, Thais N.; Fromm, Lukas; Döpper, Tibor; Görling, Andreas; Libuda, Jörg (Journal of Physical Chemistry Letters, 2018)
We have studied the anchoring mechanism of a phosphonic acid on an atomically defined oxide surface. Using time-resolved infrared reflection absorption spectroscopy, we investigated the reaction of deuterated phenylphosphonic acid (DPPA, C6HsPO3D2) with an atomically defined Co3O4(111) surface in situ during film growth by physical vapor deposition. We show that the binding motif of the phosphonate anchor group changes as a function of coverage. At low coverage, DPPA binds in the form of a chelating tridentate phosphonate, while a transition to a chelating bidentate occurs close to monolayer saturation coverage. However, the coverage-dependent change in the binding motif is not associated with a major change of the molecular orientation, suggesting that the rigid phosphonate linker always maintains the DPPA in a strongly tilted orientation irrespective of the surface coverage.